2022
DOI: 10.3389/fonc.2021.802727
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy to Identify ceRNA-Based CCDC144NL-AS1/SERPINE1 Regulatory Axis as a Novel Prognostic Biomarker for Stomach Adenocarcinoma via High Throughput Transcriptome Data Mining and Computational Verification

Abstract: Stomach adenocarcinoma (STAD) is one of the most malignant cancers that endanger human health. There is growing evidence that competitive endogenous RNA (ceRNA) regulatory networks play an important role in various human tumors. However, the complexity and behavioral characteristics of the ceRNA network in STAD are still unclear. In this study, we constructed a ceRNA regulatory network to identify the potential prognostic biomarkers associated with STAD. The expression profile of lncRNA, miRNA, and mRNA was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…In recent years, bioinformatics research related to transcriptomic studies and high-throughput sequencing have led to the discovery of more and more genes involved in driving. A few studies have found a novel prognostic biomarker for STAD by high throughput transcriptome data mining 5 . The tumor microenvironment (TME) refers to the non-cancerous cells and components that are presented in the tumor, including the molecules they produce and release.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, bioinformatics research related to transcriptomic studies and high-throughput sequencing have led to the discovery of more and more genes involved in driving. A few studies have found a novel prognostic biomarker for STAD by high throughput transcriptome data mining 5 . The tumor microenvironment (TME) refers to the non-cancerous cells and components that are presented in the tumor, including the molecules they produce and release.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, according to the information of multivariate survival analysis, the pooled HRs with 95% CI was calculated. Four studies (23,(27)(28)(29) with clear basis of HR examination were considered for pooled examination of multivariate reports. Furthermore, lncRNAs which were reported at least three times according to the univariate or multivariate survival analysis were meta-analized.…”
Section: Discussionmentioning
confidence: 99%
“…Among the included studies in the current meta-analysis, three (22,24,29) and two (19,23) studies introduced CCDC144NL-AS1 and LINC01094 as prognostic biomarkers in GC, respectively. As mentioned above, three ceRNA network studies reported CCDC144NL-AS1 as prognostic biomarker in GC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations